Microwave-Assisted Freeze-Drying: Impact of Microwave Radiation on the Quality of High-Concentration Antibody Formulations - Nicole Härdter; Raimund Geidobler; Ingo Presser; Gerhard Winter (MDPI AG, 2023)
Microwave-assisted freeze-drying (MFD) offers significant time savings compared to conventional freeze-drying (CFD). While a few studies have investigated the stability of biopharmaceuticals with low protein concentrations after MFD and storage, the impact of MFD on high-concentration monoclonal antibody (mAb) formulations remains unclear. In this study, we systematically examined the effect of protein concentration in MFD and assessed protein stability following MFD, CFD, and subsequent storage using seven protein formulations with various stabilizers and concentrations. We demonstrated that microwaves directly interact with the active pharmaceutical ingredient (API), leading to decreased physical stability, specifically aggregation, in high-concentration antibody formulations. Furthermore, typically used sugar:protein ratios from CFD were insufficient for stabilizing mAbs when applying microwaves. We identified the intermediate drying phase as the most critical for particle formation, and cooling the samples provided some protection for the mAb. Our findings suggest that MFD technology may not be universally applicable to formulations well tested in CFD and could be particularly beneficial for formulations with low API concentrations requiring substantial amounts of glass-forming excipients, such as vaccines and RNA-based products.